Determinan Kepatuhan Wajib Pajak Orang Pribadi Dimoderasi Profesionalisme Account Representative - Selma Putri Safira; Indrawati Yuhertiana (Owner : Riset dan Jurnal Akuntansi, 2023)
This study aims to test and find empirical evidence on the factors that determine individual taxpayer compliance moderated by Account Representative Professionalism (Empirical Study at KPP Pratama Surabaya Mulyorejo). The sample used in this study is active taxpayers who are registered at KPP Pratama Surabaya Mulyorejo. Data was collected using one of the non-probability sampling methods, namely incidental sampling. Data collection by distributing questionnaires to WPOP. The number of questionnaires distributed was 100 questionnaires. This study uses a multiple regression model whose management is carried out with the SmartPLS 3.0 software program. The analysis in this study includes two measurements, namely: outer model measurements such as convergent & discriminant validity tests, and reliability tests; and, inner model measurements (goodness of inner model) such as R-Square, path coefficients, and moderation tests. The results of the analysis use the outer model measurement with all variables having a significant effect on taxpayer compliance. Then the measurement of the inner model (goodness of inner model) uses R-Square with e-filling system variables, tax socialization, tax sanctions, and Account Representative professionalism of 39.9%, while the remaining 60.1% is influenced by other variables. Measurement of the inner model using the path coefficients test states that the e-filling system variables, tax sanctions have a positive and significant effect on taxpayer compliance, while the tax socialization variable has a negative and significant effect on taxpayer compliance. The last measurement of the inner model using the moderation test explains that the Account Representative's professionalism towards the e-filling system variable & tax sanctions can be said to be a predictor moderating variable, while to the tax socialization variable it can be said to be a potential moderating variable. So based on the conclusion, that the e-filling system and tax sanctions have a significant effect on taxpayer compliance, while tax socialization has no significant effect on taxpayer compliance. And the professionalism of Account Representatives is not able to moderate the influence of the e-filling system, tax socialization, or tax sanctions